Cross-shelf and vertical structure of pelagic amphipods (Crustacea) related to hydro-meteorological conditions in the neritic zone, southern Gulf of Mexico - Marco Violante-Huerta; Laura Sanvicente-Añorve; Miguel Alatorre-Mendieta; Edlin Guerra-Castro (PLoS ONE, 2025)
The environmental drivers that effect the pelagic amphipod communities in the neritic province have received little attention worldwide. This study analyzed the influence of fluvial discharges and wind regime on the pelagic amphipods in neritic waters of the southern Gulf of Mexico during two contrasting seasons: May ( dry , lower discharges and wind speeds) and November ( nortes , higher discharges and wind speeds). Zooplankton samples were collected at five depth levels of the water column (0–6, 6–12, 12–18, 45–55, and 95–105 m) using a stratified opening-closing net system. Environmental gradients were assessed by defining three horizontal assemblages (‘coastal’, ‘neritic’, ‘slope’) and two vertical assemblages (‘surface’: 0–18 m; ‘deep’: 45–105 m). Seasonally, the greater volume of nutrient-rich discharges during nortes resulted in a higher amphipod density. Spatially, low salinity waters off river mouths corresponded to the lowest amphipod density and diversity. The horizontal and vertical assemblages showed significant differences during the dry (ANOSIM test, p < 0.05); during nortes , the structure of horizontal and vertical assemblages showed a lower heterogeneity, probably due to wind strength. Differences within the assemblages defined in the horizontal and vertical planes were only evident when Lestrigonus bengalensis was considered in the analysis; however, without this species, the amphipod community showed more homogeneity across the two seasons. Anchylomera blossevillei, Tetrathyrus forcipatus, and the juveniles of Eupronoidae were ecologically relevant in the characterization of the assemblages due to their specific environmental requirements. Diversity, evaluated using the completeness method, increased from the coast to the ocean in both seasons; vertically, diversity was highest in the ‘deep’ assemblage during the dry , but no differences were observed between assemblages in nortes . The greater similarity of the assemblages during nortes was associated with a higher homogeneity in hydrological conditions due to the strong winds that dominate this season. These findings contribute to a deeper ecological understanding of the effects of hydro-meteorological conditions on the structure of pelagic amphipod communities.